2019
DOI: 10.1002/adhm.201900660
|View full text |Cite
|
Sign up to set email alerts
|

Antigen‐Inorganic Hybrid Flowers‐Based Vaccines with Enhanced Room Temperature Stability and Effective Anticancer Immunity

Abstract: Particle‐based antigen carriers as adjuvants play an important role in vaccine development. Herein, an antigen‐inorganic hybrid flower‐like particle is developed as a novel vaccine carrier. Model antigen ovalbumin (OVA)‐copper (II) sulfate hybrid vaccines (OVA‐Cu‐HVs) are mildly and facilely constructed through a biomimetic mineralization process. OVA‐Cu‐HVs facilitate cellular uptake in antigen‐presenting cells and the internalization of OVA‐Cu‐HVs involves macropinocytosis‐mediated endocytosis. OVA‐Cu‐HVs ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…R837-aOVA-ApoE3-HNP, a bionic nano vaccine, one of its components is a membrane phospholipid loaded with antigen ovalbumin (OVA), and it can use macropinocytosis to facilitate antigen presentation of DCs (171). OVA-Cu-HVs, a hybrid vaccine composed of antigen ovalbumin (OVA) and copper (II) sulfate (Cu), was manufactured to serve as a new vector related to macropinocytosis (172). DBMs, drug-loaded anthracyclineloaded bacterial magnetosomes with enhanced anticancer efficiency, can be internalized into HepG2 cells through caveolaemediated macropinocytosis and endocytosis (173).…”
Section: Proteinsmentioning
confidence: 99%
“…R837-aOVA-ApoE3-HNP, a bionic nano vaccine, one of its components is a membrane phospholipid loaded with antigen ovalbumin (OVA), and it can use macropinocytosis to facilitate antigen presentation of DCs (171). OVA-Cu-HVs, a hybrid vaccine composed of antigen ovalbumin (OVA) and copper (II) sulfate (Cu), was manufactured to serve as a new vector related to macropinocytosis (172). DBMs, drug-loaded anthracyclineloaded bacterial magnetosomes with enhanced anticancer efficiency, can be internalized into HepG2 cells through caveolaemediated macropinocytosis and endocytosis (173).…”
Section: Proteinsmentioning
confidence: 99%
“…Laccase@Co 3 (PO 4 ) 2 •HNFs retained 50% of their activity after incubation at pH 9.5 for 3 h, where the free laccase almost lost all of its activity. It should be noted that the stability of laccase@Co 3 (PO 4 ) 2 •HNFs was lower than the free enzyme in acidic pH values due to the solubility of cobalt phosphate in acidic pH 25 . No data is available for comparison.…”
Section: Resultsmentioning
confidence: 97%
“…HNFs-based biocatalysts have been incorporated for the removal of organic contaminations such as phenolic compounds and industrial dyes 23 . Also, due to the pH-responsive release of the immobilized biomolecule, HNFs have been incorporated as a drug delivery platform 25 . It has been reported that after incorporating enzymes into HNFs, their activity, stability, and reusability have notably increased, owing to low mass transfer limitations arising from their high surface-to-volume ratio and cooperative effects between enzymes and metal ions 26 .…”
Section: Introductionmentioning
confidence: 99%